Thermodynamic model for biomass processing in pressure intensified technologies - Gonzalez Prieto, Mariana (2014)
Pressure intensified technologies have a great potential in the context of biomass refining. A thermodynamic model able to predict phase behavior oftypical mixtures found in biomass processing technologies, containing for instance hydrocarbons, organo-oxygenated compounds and water, is required for the development of a biorefinery process simulator. Moreover, the design of particular fuel/biofuel blends also requires the support of a thermodynamic model to predict the properties of the final products. These types of mixtures are highly non-ideal due to the presence of association and solvation effects. It has already been proved that the Group Contribution with Association Equation of State (GCA-EoS) is able to predict the complex phase behavior of mixtures containing natural products and biofuels. In the last few years, several contributions agree that 2,5-dimethylfuran has a great potential as a sugar-derived fuel additive. In this work, as a case study, we extend the GCA-EoS to represent the phase equilibria of furan derivatives with hydrocarbons and alcohols. In addition, we show that the GCA-EoS is able to predict, based on the performed parameterization, high pressure data of 2,5-hydroxymethylfurfural solubility in CO2 and ethanol as co-solvent.